2013
DOI: 10.15288/jsad.2013.74.746
|View full text |Cite
|
Sign up to set email alerts
|

Early Risk Factors for Alcohol Use Across High School and Its Covariation With Deviant Friends

Abstract: ABSTRACT. Objective: Past research has associated childhood characteristics and experiences with alcohol use at single time points in adolescence. Other work has focused on drinking trajectories across adolescence but with risk factors typically no earlier than middle or high school. Similarly, although the connection between underage drinking and affi liation with deviant friends is well established, early risk factors for their covariation across adolescence are uncertain. The present study examines the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…This increase in resemblance for alcohol use coincides with the age when offspring are both initiating alcohol use and living with their parents. This may be a maximal time in which they are modeling parental behaviors and would be consistent with prior research (Armstrong et al, 2013;Koning et al, 2010;Latendresse et al, 2008). There were no significant differences in the parent-offspring correlations from age 17 to age 24, followed by a significant decrease in resemblance at age 29.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This increase in resemblance for alcohol use coincides with the age when offspring are both initiating alcohol use and living with their parents. This may be a maximal time in which they are modeling parental behaviors and would be consistent with prior research (Armstrong et al, 2013;Koning et al, 2010;Latendresse et al, 2008). There were no significant differences in the parent-offspring correlations from age 17 to age 24, followed by a significant decrease in resemblance at age 29.…”
Section: Discussionsupporting
confidence: 86%
“…Of additional importance is whether parental alcohol use and problems are related to offspring alcohol use. Parental alcohol use has been shown to predict the onset of and overall offspring alcohol use (Alati et al, 2014;Armstrong et al, 2013;Brook et al, 2010;Kelly et al, 2011;Latendresse et al, 2008;Shortt et al, 2007), whereas parental alcohol problems have been shown to predict both alcohol use and problems in offspring (Kendler et al, 2013;Latendresse et al, 2008). There is some inconsistency in these findings, however, depending on offspring age, suggesting that the association of offspring alcohol use and problems with respective parental measures may increase across adolescent development (Kendler et al, 2013;Latendresse et al, 2008).…”
Section: T Here Is a Strong Progression Of Alcohol Use And Problems Omentioning
confidence: 99%
See 1 more Smart Citation
“…However, the match between personality and parenting style has a strong impact on initiation and progression of substance use during adolescence. While effective, “authoritative” parenting is effective overall, the pairing of an impulsive, acting out adolescent and authoritarian rather than authoritative parent is a risk factor which increases the risk of substance abuse by adolescents (Armstrong et al, 2013). Finally, other activities in the life of adolescents have a protective effects, especially engagement in religious activities and sports (Agrawal & Lynskey, 2009; Metzger, Dawes, Mermelstein, & Wakschlag, 2011; Nasim, Belgrave, Jagers, Wilson, & Owens, 2007; Silins et al, 2013) Engagement is sports is especially protective against initiation of smoking (Adachi-Mejia, Gibson Chambers, Li, & Sargent, 2014).…”
Section: Intrinsic and Extrinsic Factors That Influence Initiatiomentioning
confidence: 99%
“…A fifth longitudinal study conducted by Armstrong et al (2013) and using the same sample as Burk et al (2011) followed 374 participants from 3.5 years until Grade 12 and modeled alcohol use quantity from Grades 9 to 12 with a quadratic growth curve and the intercept centered at Grade 9. They assessed disinhibition, authoritative parenting and authoritarian parenting in childhood.…”
Section: Reactivitymentioning
confidence: 99%